Size-Dependent EPR Effect of Polymeric Nanoparticles on Tumor Targeting - Kang, Homan; Rho, Sunghoon; Stiles, Wesley R.; Hu, Shuang; Baek, Yoonji; Hwang, Do Won; Kashiwagi, Satoshi; Kim, Moon Suk; Choi, Hak Soo (Advanced Healthcare Materials, 2020)
Passive targeting of large nanoparticles by the enhanced permeability and retention (EPR) effect is a crucial concept for solid tumor targeting in cancer nanomedicine. There is, however, a trade-off between the long-term blood circulation of nanoparticles and their nonspecific background tissue uptake. To define this size-dependent EPR effect, near-infrared fluorophore-conjugated polyethylene glycols (PEG-ZW800s; 1–60 kDa) are designed and their biodistribution, pharmacokinetics, and renal clearance are evaluated in tumor-bearing mice. The targeting efficiency of size-variant PEG-ZW800s is investigated in terms of tumor-to-background ratio (TBR). Interestingly, smaller sized PEGs (≤20 kDa, 12 nm) exhibit significant tumor targeting with minimum to no nonspecific uptakes, while larger sized PEGs (>20 kDa, 13 nm) accumulate highly in major organs, including the lungs, liver, and pancreas. Among those tested, 20 kDa PEG-ZW800 exhibits the highest TBR, while excreting unbound molecules to the urinary bladder. This result lays a foundation for engineering tumor-targeted nanoparticles and therapeutics based on the size-dependent EPR effect.
Keywords: Enhanced permeability and retention effects; Enhanced permeability and retentions; Near-infrared fluorophores; Polymeric nanoparticles; Renal clearance; Targeted nanoparticle; Tumor targeting; Tumor to background ratios; Animals; Antineoplastic Agents; Area Under Curve; Fluorescent Dyes; Half-Life; HeLa Cells; Humans; Kidney; Male; Mice; Mice, Nude; Molecular Weight; Nanomedicine; Nanoparticles; Neoplasms; Particle Size; Polyethylene Glycols; ROC Curve; Tissue Distribution; Xenograft Model Antitumor Assays; enhanced permeability and retention; pharmacokinetics; poly(ethylene glycol); renal clearance; tumor targeting